UPAYA PERTAMA PENYUSUNAN METODA PERHITUNGAN MODEL SEBARAN PERJALANAN BERBASIS DATA ARUS LALU LINTAS(Kasus Percobaan Sederhana: 4 Zona, 4 Ruas, Sebaran Seragam, Pembebanan All-or-Nothing Murni) - Hitapriya Suprayitno (Jurnal Teknobisnis, 2005)
Transportation demand model plays an important role in transportation planning. Synthetic model development seems to be very complicated since it's always time and money consuming. This, the more practical and simpler modenling method becomes a great necessities. The recent idea is using traffic flow data to develop an origin destination matrix. The objective of this research is to develop a distribution model based on a traffic flow data. A very simple model having 4 zones, 4 links, uniform distribution, and basic all-or-nothing assignment, had .been used as a study case. The result show that the mathematical model is a simultaneous linear equations model. Since the number of linear equations developed based on traffic flow data is less than the number of origin destination matrix cells, 4 trip production